SYNTHESIS AND CARATERIZATION OF SNO2 AS A DEVELOPMENT EFFORTS WHITE TIN PRODUCTS TO IMPROVE NATIONAL DEVISES - Anti Kolonial Prodjosantoso; Endang Widjajanti Laksono; M. Pranjoto Utomo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
Long-term goal of this research is to apply nanotechnology in the development of downstream products of tin to increase the national foreign exchange. As a preliminary study, SnO2 was synthesized by dissolving tin metal in concentrated HCl followed by addition of concentrated NH4OH in dropwise. The precipitate was filtered, dried, and partially characterized using IR spectrophotometer FTIR-8300/8700 model in the range of wave number of 400 cm-1 to 4000 cm-1, whilst the rest was then heated in a furnace at temperature about 900 °C for 4 hours. The oxide was then cooled and characterized by using XRD Zhimadsu S6000 diffractometer using monochromatic Cu KĮ radiation with a wavelength (Ȝ) of 1.5406 Å in the 2ș range 5o to 90o , and scanning electron microscope (SEM) JEOL T330 A operating at 15 keV. The crystallography aspects of SnO2 was studied based on the X-ray diffraction data (XRD) which was analyzed with Rietveld method using the WinPLOTR program. The SnO2 oxide was found to be tetragonal P42/mnm space group having lattice parameters of a = b = 4.7337(2) ǖ and c = 3.1841(3) ǖ. The particle size of the SnO2 oxide was found to be about 35.39 nm.